RISK FACTORS DETERMINANTS ANEMIA EVENTS IN ADOLESCENT PUSKESMAS IN KOTA SELATAN - Endah Yulianingsih; Hasnawatty Surya Porouw (Alma Ata University Press, 2020)
Anemia is a global public health problem that needs special attention. Anemia in adolescent girls is a common problem, especially in developing countries (WHO, 2008). Anemia is a health problem that is most often found in developed and developing countries, including Indonesia. The prevalence of anemia in Indonesia is not so far from the global anemia prevalence rate, which is 21.7%, where the prevalence of anemia has entered the category of public health problems. moderate so this should receive special attention. Adolescents are an age group that is very at risk of anemia because nutritional needs, especially iron, exceed the needs of other age groups due to accelerated growth and increased physical activity. This study aims to determine the factors associated with the incidence of anemia in adolescent girls in the working area of Puskesmas Kota Selatan, Gorontalo City. This type of research is cross-sectional using the bivariate test with the chi square test and the multivariate test with logistic regression. The research instrument used a questionnaire. The results of this study indicate that there is a relationship between age at menarche (p = 0.001), knowledge (p = 0.000), maternal education (p = 0.000), menstrual pattern (p = 0.000), BMI (p = 0.009), menstruation (p = 0.003). The most dominant factor for the incidence of anemia in adolescent girls in the work area of Puskesmas Kota Selatan Kota Gorontalo is the knowledge factor with a p value of 0.001 exp B = 2,650 (CI 1.643-4770) which means that respondents who have good knowledge will have a chance of 2.6 times more. can prevent anemia which is controlled by variable menstrual patterns, menstrual age and mother's education.